Deciphering metabolic traits of the fungal pathogen Aspergillus fumigatus: redundancy vs. essentiality - Amich, Jorge; Krappmann, Sven (Frontiers in Microbiology, 2012)
Incidence rates of infections caused by environmental opportunistic fungi have risen over recent decades. Aspergillus species have emerged as serious threat for the immunecompromised, and detailed knowledge about virulence-determining traits is crucial for drug target identification. As a prime saprobe, A. fumigatus has evolved to efficiently adapt to various stresses and to sustain nutritional supply by osmotrophy, which is characterized by extracellular substrate digestion followed by efficient uptake of breakdown products that are then fed into the fungal primary metabolism. These intrinsic metabolic features are believed to be related with its virulence ability. The plethora of genes that encode underlying effectors has hampered their in-depth analysis with respect to pathogenesis. Recent developments in Aspergillus molecular biology allow conditional gene expression or comprehensive targeting of gene families to cope with redundancy. Furthermore, identification of essential genes that are intrinsically connected to virulence opens accurate perspectives for novel targets in antifungal therapy.